Differences in priority by age group and perspective: implications for public health education and campaigning in relation to dementia. (18th July 2018) - Haapala, Irja; Carr, Ashley; Biggs, Simon
ABSTRACT: Objectives: A shift toward public health responses to dementia, raises questions about the most appropriate approaches to specific population groups. We examined perspective and age as elements in effective campaigning. Implications from the standpoint of the recipient are drawn for public health education and practice. Design: In-depth semi-structured face-to-face and telephone interview with self-selected participants recruited via adverts, contact with provider organizations and cards placed in retail and service settings. Questions focused on attitudes to dementia and expectations of public campaigning and education. Setting: Community-dwelling adults were interviewed across five Australian states. Participants: A total of 111 people from 5 target groups: people with dementia ( n = 19), carers ( n = 28), care work and service professionals from healthcare ( n = 21), social work ( n = 23) and commercial service professions ( n = 20) involving people in younger adulthood ( n = 13), early midlife ( n = 23), later midlife ( n = 54), and older age ( n = 21). Measurements: All interviews were transcribed and analyzed thematically by three researchers, reaching consensus before coding and further analysis in NVivo. Narrative analysis of transcripts included 330 topics relating to 6 main areas of focus. Results: Attitudes and views on effective future campaigning reflected a desire for greater social inclusion, but did not focus on prevention and health services. Professionals focused on increasing interpersonal skills, people with dementia on normalization, and carers on awareness-raising. Conclusions: Public health campaigning and education in relation to dementia, could benefit from closer consideration of perspective and age of recipient in intervention design. Interpersonal skills and social inclusion were identified as key issues.